Radical Scavenging Activity of the Pistacia terebinthus in Fenton Reagent Environment and Its Protective Effects on the Unsaturated Fatty Acids - Yilmaz, Okkes; Ozsahin, Ayse Dilek; Bircan, Burak; Erden, Yavuz; Karaboga, Zeynep (Asian Journal of Chemistry, 2010)
This study investigated protective effects of the Pistacia terebinthus extracts on the unsaturated fatty acids and the prevention of lipid peroxidation formation in the Fenton reagent environment. Antioxidative activities of the Pistacia terebinthus extracts were determined with the following modifications. Lipid peroxidation level in the Fenton R group significantly high compared to control group, but lipid peroxidation in the Pistacia terebinthus extract groups significantly decreased according to the Fenton R group (p<0.0001). In addition, it was determined that Pistacia terebinthus extracts had scavenging effect on the DPPH radical depending on the increase in flavonoid concentration. The fatty acid levels in the Fenton R group were lower than the control group (p<0.001). However, fatty acid levels in the P terebinthus extract groups were higher than the Fenton R group (p<0.001). Present results confirm that the Pistacia terebinthus extracts decrease lipid peroxidation level in the Fenton reagent environment and protects markedly unsaturated fatty acids in the environment with radical sourced oxidations.
Keywords: Lipid peroxidation; Fenton reagent; Pistacia terebinthus; flavonoids; Radical scavenging effects